Parrots of the world - Forshaw, Joseph Michael (Princeton field guides., 2010)
From the macaws of South America to the cockatoos of Australia, parrots are among the most beautiful and exotic birds in the world--and also among the most endangered. This stunningly illustrated, easy-to-use field guide covers all 356 species and well-differentiated subspecies of parrots, and is the only guide organized by geographical distribution--Australasian, Afro-Asian, and neotropical. It features 146 superb color plates depicting every kind of parrot, as well as detailed, facing-page species accounts that describe key identification features, distribution, subspeciation, habitat, an.